the Role of English Songs in Enhancing Speaking Skill in Al-Khoirot Islamic Boarding School - budik, kusworo (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
This study explores the role of English song in enhancing speaking skills among santri at Al-Khoirot Islamic Boarding School. Recognizing that traditional classroom methods often emphasize reading and writing, the research focuses on how music, particularly English songs, can supplement these approaches by improving students’ oral communication. Using a descriptive qualitative method, data were collected through semi-structured interviews with five santri who frequently listen to English music. Thematic analysis was applied to identify recurring patterns and insights. The findings reveal that English music plays a significant role in improving students’ pronunciation, vocabulary, and speaking fluency. Listening to songs helped learners become more familiar with native pronunciation and natural intonation, while repetition in lyrics supported vocabulary retention. Additionally, the study shows that music enhances students’ motivation, reduces learning anxiety, and creates a more engaging environment for language acquisition. Although its effect on listening comprehension was noticeable, it was less pronounced than its impact on speaking skills. Importantly, students emphasized the need for song selection that aligns with Islamic values and is appropriate for their language level. The study concludes that English music, when properly integrated and supported with interactive activities, can serve as a valuable tool to enrich speaking.